2019
DOI: 10.3892/ol.2019.11061
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Holliday junction recognition protein predicts poor prognosis and biochemical recurrence in patients with prostate cancer

Abstract: Abnormal expression of Holliday junction recognition protein (HJURP) in several types of tumor cells plays a vital role in the formation and progression of tumors. Few studies have investigated the role of HJURP in prostate cancer (PCa). The aim of this study was to analyze the expression levels of HJURP in PCa and to establish the association with clinicopathological data. Reverse transcription quantitative polymerase chain reaction and immunohistochemical analysis were used to detect the expression levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
2
14
1
Order By: Relevance
“…Interestingly, the subcellular location of HJURP was initially reported to be nucleus 4 , however, we found that it was mainly stained in the cytoplasm of PCa cells according to the IHC. This is consistent with prior studies in PCa 10 . In addition, in hepatocellular carcinoma 12 , 26 , HJURP is also stained in the cytoplasm.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Interestingly, the subcellular location of HJURP was initially reported to be nucleus 4 , however, we found that it was mainly stained in the cytoplasm of PCa cells according to the IHC. This is consistent with prior studies in PCa 10 . In addition, in hepatocellular carcinoma 12 , 26 , HJURP is also stained in the cytoplasm.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, HJURP is an unfavorable factor in PCa 10 , but the specific functions and mechanisms underlying its involvement remain unclear. In this study, we demonstrated that HJURP was upregulated in PCa and its expression was positively correlated with unfavorable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of HJURP was downregulated at the mRNA and protein expression levels in RCC cell lines and tissues. This result is in contrast with studies on other types of cancer (4,(14)(15)(16), suggesting that the specific role of HJURP varies and is tissue-dependent, and may be associated with organ specificity, or highlights the possibility that HJURP may exert its effects on different target genes in different tissues (36)(37)(38). In the present study, overexpression of HJURP in RCC cells reduced colony formation and cell growth.…”
Section: Discussioncontrasting
confidence: 99%
“…HJURP is a histone chaperone involved in the recruitment of de novo histone H3 variants CenH3 (CENP-A) and CENP-C in nucleosomes, which can regulate the ampli cation of centromeric chromatin and chromosomal stability [36] . HJURP has been con rmed as a key prognostic-related gene in breast cancer, hepatocellular carcinoma, advanced serous ovarian cancer, colorectal cancer and prostate cancer [37][38][39][40][41] . There are reports showing that HJURP promotes tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%